2021
DOI: 10.1021/acs.macromol.1c00152
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Bond Association-Mediated Dynamics and Viscoelastic Properties of Tough Supramolecular Hydrogels

Abstract: Forming robust associative interactions has been an effective strategy for the design of tough hydrogels. However, the role of associative interactions in the dynamics of hydrogels still remains elusive. Here, we report a series of poly­(acrylamide-co-methacrylic acid) hydrogels with moderate water contents and excellent mechanical properties that are facilely synthesized by free-radical copolymerization. The mechanical properties of these hydrogels vary with the feeding molar fraction of acrylamide (f am). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
87
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 111 publications
(92 citation statements)
references
References 65 publications
5
87
0
Order By: Relevance
“…The relatively low modulus of the glassy hydrogel is due to the strong plasticizing effect of water that weakens the strength of associative interactions between the polymer chains . Similar phenomena have been found in other glassy hydrogels with dense hydrogen bonds or polyelectrolyte complexes. ,, …”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…The relatively low modulus of the glassy hydrogel is due to the strong plasticizing effect of water that weakens the strength of associative interactions between the polymer chains . Similar phenomena have been found in other glassy hydrogels with dense hydrogen bonds or polyelectrolyte complexes. ,, …”
Section: Resultssupporting
confidence: 54%
“…As shown in Figure e, the frequency-sweep spectra of the MC-3-1/10 hydrogel at different temperatures converge to a master curve by time–temperature superposition (TTS). The validity of TTS to PESC hydrogel at a relatively low test temperature should be related to the stable network structure with robust physical cross-links, , in which the hydrophobic interaction enhances and stabilizes the electrostatic interaction between the surfactants and PMAAc chains. The apparent activation energy value E a is calculated as 137 kJ/mol from the Arrhenius plot of the shift factor α T (Figure e,f), indicating the high strength of PESCs.…”
Section: Resultsmentioning
confidence: 99%
“…These results imply that these samples developed cross‐linked structures via photo‐polymerization due to the introduction of the PEEL as a physical cross‐linker 41,42,49 . Generally, the G ′ value increased with increasing the hydrogen bonding strength due to the aspect of the increased hydrophobic surrounding in the physical cross‐linked networks system 50–52 . Along with, in this system, the G ′ value of all the samples increased with a larger proportion of DUCA.…”
Section: Resultsmentioning
confidence: 82%
“…41,42,49 Generally, the G 0 value increased with increasing the hydrogen bonding strength due to the aspect of the increased hydrophobic surrounding in the physical cross-linked networks system. [50][51][52] Along with, in this system, the G 0 value of all the samples increased with a larger proportion of DUCA. For example, CPNs-5 (DUCA networks) has a much higher G 0 value than that of CPNs-1 (DUA networks), which results in the higher G 0 value of cross-linked CPNs with a higher proportion of DUCA.…”
Section: Rheological Properties Of Crosslinked Copolymer Networkmentioning
confidence: 91%
“…Recent works showed that U ̃≈ 2−7k b T in isolated conditions. 33 Du et al 13 obtained the critical energy U ̃≈ 19k b T for hydrogen bond dissociation from the dynamic moduli spectra determined by rheological measurements.…”
Section: Dissociation Of a Hydrogen Bond Based Cross-linkmentioning
confidence: 99%